PENGARUH KOMISARIS INDEPENDEN, RETURN ON ASSETS (ROA) DAN KONEKSI POLITIK TERHADAP TAX AVOIDANCE - Gusti Deni As’yami Rahman; Mega Andani; Elma Abnaina (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
The research aims to analyze the Influence of Independent Commissioners, Return on Assets (RoA) and Political Connections on Tax Avoidance. The research method used is quantitative. The population to be used in this study is the oil, gas and natural gas sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The research sample was 12 companies. The analysis used multiple linear regression. The results of this study indicate that the Independent Commissioner Variable has no effect on tax avoidance, Return on Assets (ROA) has a negative effect, and Political Connections has a positive effect on tax avoidance.